2010
DOI: 10.1152/ajprenal.00324.2010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular conformation and filtration properties of anionic Ficoll

Abstract: The physiology of glomerular permselectivity remains mechanistically obscure, despite its importance in human disease. Although electrical contributions to glomerular permselectivity have long been considered important, two recent reports demonstrated enhanced glomerular permeability to anionic versus neutral polysaccharides. The interpretation of these observations is complicated by confounding of the effects of chemical modification on charge with effects on size and shape. In this report, neutral and anioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…In the present study we found that the sieving coefficients for aFicoll Ն35 Å in radius (for approaching or exceeding 1) significantly deviated from those predicted by the charged fibermatrix model, in that sieving coefficients for aFicoll approached those for nFicoll. A similar phenomenon has been observed for aFicoll vs. nFicoll in artificial membranes (17). This may indicate that charge restriction effects tend to be markedly reduced in magnitude when the size of the charged molecules approaches the size of the transport limiting structures of the barrier or that charge selectivity is much more complex than predicted from a charged fiber-matrix model.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In the present study we found that the sieving coefficients for aFicoll Ն35 Å in radius (for approaching or exceeding 1) significantly deviated from those predicted by the charged fibermatrix model, in that sieving coefficients for aFicoll approached those for nFicoll. A similar phenomenon has been observed for aFicoll vs. nFicoll in artificial membranes (17). This may indicate that charge restriction effects tend to be markedly reduced in magnitude when the size of the charged molecules approaches the size of the transport limiting structures of the barrier or that charge selectivity is much more complex than predicted from a charged fiber-matrix model.…”
Section: Discussionsupporting
confidence: 70%
“…The electric charge of the aFicoll used in the experiments has been quantified in terms of the zeta potential (see Fig. 1), which is the electric potential at the slipping plane, with values of Ϫ40 mV and Ϫ45 mV for CM-Ficoll 70 and CM-Ficoll 400, respectively (17). The surface charge density can be approximated using the Grahame equation…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that the observed hyperpermeability, both in vivo and in vitro, in Ficoll solutions is unlikely to originate from shear-induced conformational changes. In systematic studies of the larger branched polymer Ficoll PM400 bimodal distributions were observed in size exclusion chromatography experiments (SEC) [2,29]. The findings suggest that Ficoll PM400 may contain two distinct size distributions, although the lower molecular mass material could not be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…The basis for the apparently paradoxical effect was attributed either to an absence of electrostatic hindrance or to conformational differences between neutral and anionic Ficoll (2,25). To probe this question more deeply, our group developed an anionic Ficoll that appeared to be conformationally similar to neutral Ficoll and was retarded by anionic membranes (24). Having completed some very preliminary studies on solute partitioning by extracellular matrices, we sought evidence to support either enhanced or retarded transmission of anionic polysaccharides through a model of the GBM.…”
mentioning
confidence: 99%